KESESUAIAN LOKASI KULIAH KERJA NYATA (KKN) DENGAN ARAH PEMBANGUNAN DAERAH DI KABUPATEN CILACAP - Muhammad Husnul Maab; Suryo Wibisono; Purwanto Kurniawan (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Development is a force in realizing social welfare and political progress, both at the local and national levels. Even though local government has autonomous rights, the district still has a big responsibility for locals progress. In addition, academics are obliged to apply science and technology practically so that they can be used by the community to improve welfare. Therefore, the suitability of the location for the implementation of community service in the form of Kuliah Kerja Nyata (KKN) needs to be adjusted to the direction of regional development. With the quantitative descriptive research method, the village data where the KKN was implemented in 2019-2021 were compared with the village data of regional development priorities. The results showed that the majority of KKN locations were not included in the list of development priority villages, both in poor villages, innovation villages, tourist villages, and stunting villages. Only a small number of KKN implementation locations are in accordance with the direction of regional development, especially in poor villages. Possibly caused by the licensing system for community service activities that have not been implemented optimally. For this reason, it is necessary to maximize the function of the licensing system in order to direct community service activities to be in line with the direction of regional development.